1993
DOI: 10.1111/j.1464-410x.1993.tb15880.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Exercise versus Surgery in the Treatment of Impotence

Abstract: A group of 150 consecutive male patients with erectile dysfunction and proven venous leakage were randomised either to surgery or to a pelvic floor training programme. The operative procedure consisted of dissection and removal of the deep dorsal vein of the penis and its tributaries or large veins that drain into the internal or external pudendal system. The training programme was given 5 times, in weekly sessions, and the patients were supervised by trained physiotherapists. Surgery was not superior to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 18 publications
1
22
0
4
Order By: Relevance
“…21,22 Few studies have evaluated the effects of pelvic-floor exercises in the EF. 23,24,30,31 Although they suggest an improvement of EF with pelvic-floor exercises, they are methodologically inadequate. Patients included in those studies had various causes of ED and underwent different intervention methods.…”
Section: 15--1729mentioning
confidence: 99%
“…21,22 Few studies have evaluated the effects of pelvic-floor exercises in the EF. 23,24,30,31 Although they suggest an improvement of EF with pelvic-floor exercises, they are methodologically inadequate. Patients included in those studies had various causes of ED and underwent different intervention methods.…”
Section: 15--1729mentioning
confidence: 99%
“…As illustrated in figure 1, an increase of intracavernous pressure and an inhibition of venous leakage by voluntary pelvic floor contraction could be documented by cavernosometry and cavernosography. Since Baert and co-workers [10, 11, 12]showed that in the long-term follow-up pelvic floor exercise led to better results compared to venous surgery, especially in moderate and medium grade venous leakage, a strengthening of the ischiocavernous muscles seems to be a reasonable approach to treat veno-occlusive dysfunction. Regular pelvic floor exercise can be achieved by a physiotherapist which seems to be a time-consuming and expensive procedure, or an advantageous transcutaneous electrical stimulation which is the standard therapy for the treatment of posttraumatic atrophy of the striated muscular system [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that physiotherapeutic measures alone, in cases of venal leakage, lead to the same results just like surgery of the leakage itself [3], allows for an assumption of an independent character of renal leakage.…”
Section: Discussionmentioning
confidence: 99%